2009
DOI: 10.1177/0021998309339636
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-Disk Type Microbond Pull-Out Test for Evaluating Fiber/Matrix Adhesion in Composites

Abstract: Adhesion strength between epoxy resin and carbon fiber was analyzed using various microbond types adhered onto a single carbon fiber. Experimental pull-out tests were performed for a quasi-disk type, a hemispherical type and a droplet type microbond specimen. The quasi-disk type microbond specimen showed high regression coefficient and low standard deviation in the measurement of interfacial shear strength data as compared with the droplet and hemispherical ones. Average value of interfacial shear strength for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…First, experimental pull-out tests were carried out to calculate the maximum pull-out load (Figure 2, entries 1 and 2, and Figure S3). As reported elsewhere [16], assuming a homogeneous stress distribution along the interface, the IFSS can be calculated as [36]:…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, experimental pull-out tests were carried out to calculate the maximum pull-out load (Figure 2, entries 1 and 2, and Figure S3). As reported elsewhere [16], assuming a homogeneous stress distribution along the interface, the IFSS can be calculated as [36]:…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the failure mechanism in composites can be fairly characterized by a fiber bundle pull-out test. In addition, the IFSS can be directly correlated with adhesion energy between the fiber and matrix, thus providing a characterization of the fiber to matrix interphase in GF-reinforced composites [16].…”
Section: Introductionmentioning
confidence: 99%
“…The shear strength measured with this new cylindrical shaped droplet was higher than that obtained by the usual sample preparation method, along with a reduction in data scatter. A quasi-disk type microbond specimen for a carbon fiber-epoxy resin developed by Choi et al [54,55] was shown to have a lower standard deviation in IFSS compared to the droplet (ellipsoid) type specimens. The loading of the quasi-disk droplet is achieved by the microvise tips and a steel section as shown in Figure 4.…”
Section: Variations and Recent Advances -Reproducibility Of Sample Preparation And Experimentsmentioning
confidence: 97%
“…15 Micromechanical modeling and experimental investigation of the microbond pull-out tests were conducted by pulling a fiber out of a quasi-disk type, a hemispherical type, or a droplet type matrix microbond specimen. [16][17][18][19][20] Nanomechanical imaging technique has been adopted for mapping the dynamic mechanical property around the interphase region. 21 Finite element analysis (FEA) model generation based on stochastic analysis on AFM images was used for fiber-matrix interphase or single fiber pull-out simulations.…”
Section: Introductionmentioning
confidence: 99%